A Comparison Study: Effects of the Group Investigation Model and Direct Instruction Model toward Science Concept Understanding (Jurnal Pendidikan IPA Indonesia, 2019)
This study aimed to compare the effects between the group investigation model and the direct instruction model toward science concept understanding in non-science first-year students. This study was a quasi-experimental research with the posttest-only control group design. This research was conducted in the Basic Sciences class in the first semester of the Islamic Education study program at Pangeran Diponegoro Islamic Institute, Nganjuk. This study used a purposive sampling technique, with one class as a control group and another as an experimental group. The type of study was a quasi-experimental research with 2x2 nonequivalent control group design factorial design. The data were analyzed using one-way ANOVA with SPSS for Windows. The test results showed that there was a difference in the average value of learning outcomes of students’ understanding in the two treatment classes, that is, the average value of learning outcomes by students experiencing group investigation model was 76.63, while the average value of learning outcomes by students experiencing the direct instruction model was 71.16. These results indicated that the investigation group had a better effect than the direct instruction model on the learning outcomes since the significance value was smaller or less than alpha 0.05 (0.000 0.05), which means that the two models applied had different influences towards learning outcomes of students’ understanding. Similarly, the average value of students who were taught by the group investigation model with high and low achievement motivation was also better than the direct instruction model with high and low achievement motivation. The analysis test showed a significance value of 0.002, which was smaller than 0.05 (0.002 0.05). It means that the group investigation model and student achievement motivation had a better influence on the learning outcomes on the students’ understanding of basic natural science concepts compared to the direct instruction model. This study aimed to compare the effects between the group investigation model and the direct instruction model toward science concept understanding in non-science first-year students. This study was a quasi-experimental research with the posttest-only control group design. This research was conducted in the Basic Sciences class in the first semester of the Islamic Education study program at Pangeran Diponegoro Islamic Institute, Nganjuk. This study used a purposive sampling technique, with one class as a control group and another as an experimental group. The type of study was a quasi-experimental research with 2x2 nonequivalent control group design factorial design. The data were analyzed using one-way ANOVA with SPSS for Windows. The test results showed that there was a difference in the average value of learning outcomes of students’ understanding in the two treatment classes, that is, the average value of learning outcomes by students experiencing group investigation model was 76.63, while the average value of learning outcomes by students experiencing the direct instruction model was 71.16. These results indicated that the investigation group had a better effect than the direct instruction model on the learning outcomes since the significance value was smaller or less than alpha 0.05 (0.000 0.05), which means that the two models applied had different influences towards learning outcomes of students’ understanding. Similarly, the average value of students who were taught by the group investigation model with high and low achievement motivation was also better than the direct instruction model with high and low achievement motivation. The analysis test showed a significance value of 0.002, which was smaller than 0.05 (0.002 0.05). It means that the group investigation model and student achievement motivation had a better influence on the learning outcomes on the students’ understanding of basic natural science concepts compared to the direct instruction model.